(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Ericsson method used to determine whether enriched sperm samples would result in offspring of a desired gender. It is used in approximately 50 centers in the United States and in many centers worldwide when scientists and andrologist discovered that sperm samples with high concentrations of either X or Y bearing sperm could be obtained. Objective:To examine the effect of Ericsson method on gender selection following intra-uterine insemination for infertile couples. Methods: One hundred infertile couples were included in this study. A programmed ovulation induction for women was done. Luteinizing hormone and estradiol hormone level were measured. Ultrasonography was used to detect the number and diameter of follicles and endometrial thickness at menstruation cycle 1 day before human chorionic gonadotropin injection. Semen analysis was done for all husbands and density gradient technique with 7% and 17% albumin concentration was performed for sperm selection in vitro. Intra-uterine insemination was accomplished and pregnancy test was done 14 days following insemination to detect the level of human chorionic gonadotropin in blood. The gender of fetus was recorded 4 months following pregnancy by ultrasonography. Results:Twenty two (22%) out of one hundred women become pregnant. According to gender, live birth babies distributed into thirteen male babies (76.64%) and only four female babies (23.36%). One pregnant woman delivered twins following intra-uterine insemination. Conclusion:It is concluded that Ericson method is a simple and effective technique for gender selection when infertile couples seek to have a baby by intra-uterine insemination. Key Words:Gender selection, Infertile couples, Intra-uterine insemination, Ericsson method.